Ultrahigh cryogenic strength and ductility in a duplex metastable ferrous medium-entropy alloy. (15th April 2023) - Gao, Qiuyu; Wei, Ran; Feng, Shilin; Chen, Chen; Han, Zhenhua; Chen, Liangbin; Wang, Tan; Wu, Shaojie; Li, Fushan
Abstract: This work presents a unique low-cost Fe62 Co5 Ni10 Cr13 Si7 Al3 (at%) medium-entropy alloy (MEA) with ultra-high strength and ductility. A duplex partially recrystallized microstructure consisting of face-centered cubic (FCC) and body-centered cubic (BCC) phases was produced by cold-rolling and short-time annealing in the MEA. In the non-recrystallized area, there are high density dislocations, and the ultra-fine grained matrix has lots of nano-precipitates. This MEA has excellent yield strength (1237 MPa and 1640 MPa) and uniform elongation (12.7% and 29.1%) at 298 K and 77 K. Additionally, due to the high multi-stage strain hardening behavior, the ultimate tensile strength of ∼2109 MPa is obtained at 77K. The excellent cryogenic mechanical properties are mainly attributed to high density dislocations, ultra-fine grains, nano-precipitates, huge Lüders deformation, hetero-deformation-induced hardening, and deformation-induced martensitic transformation. Graphical abstract: Image, graphical abstract